2014
DOI: 10.1161/strokeaha.114.004903
|View full text |Cite
|
Sign up to set email alerts
|

Age Dependence of Risk Factors for Stroke and Death in Young Patients With Atrial Fibrillation

Abstract: 8 the CHADS 2 score has been refined by use of the CHA 2 DS 2 -VASc (congestive heart failure, hypertension, age ≥75 years [doubled], diabetes, stroke/transient cerebral ischemia/thromboembolism [doubled], vascular disease [previous myocardial infarction, peripheral artery disease, or aortic plaque], age 65-74 years, sex category [female]) score. 9 The CHA 2 DS 2 -VASc score includes additional common stroke risk factors. [10][11][12] The CHA 2 DS 2 -VASc score better identifies the truly low-risk patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 24 publications
1
15
2
3
Order By: Relevance
“…30 Dissection is typically related to good prognosis, 32 a scenario complemented by the long-term follow-up of our young patients with stroke. The risk for death among young patients with atrial fibrillation has been considered low, 33 but our study shows that the risk for death is much higher among stroke patients with atrial fibrillation than among the normal population matched with age, sex, and geographical area. Our estimates of the observed and expected mortality among smaller Trial of Org 10172 in Acute Stroke Treatment subgroups may be instable, but our findings suggest that in all pathogenetic subgroups except low-risk source of cardioembolism and internal carotid artery dissection groups, the observed mortality exceeds the expected mortality in the general population.…”
Section: Discussioncontrasting
confidence: 57%
“…30 Dissection is typically related to good prognosis, 32 a scenario complemented by the long-term follow-up of our young patients with stroke. The risk for death among young patients with atrial fibrillation has been considered low, 33 but our study shows that the risk for death is much higher among stroke patients with atrial fibrillation than among the normal population matched with age, sex, and geographical area. Our estimates of the observed and expected mortality among smaller Trial of Org 10172 in Acute Stroke Treatment subgroups may be instable, but our findings suggest that in all pathogenetic subgroups except low-risk source of cardioembolism and internal carotid artery dissection groups, the observed mortality exceeds the expected mortality in the general population.…”
Section: Discussioncontrasting
confidence: 57%
“…The stroke-free survival rate was also compared between elderly patients with AF and those without AF (aged !65 years) who had none of the CHA 2 DS 2 -VASc comorbidities throughout the observation period. The magnitude of a lower stroke-free survival rate in younger patients with AF is less than that in elderly patients with AF, which is in line with the observation by Melgaard et al, 31 indicating that age is a powerful driver of stroke risk in patients with AF. Collectively, our data revealed that younger patients with AF (aged 30-55 years) who had none of the conventional CHA 2 DS 2 -VASc risk factors and were not recommended for the prevention of thromboembolic stroke 24,25 may actually have higher absolute risk of stroke than did their non-AF counterparts during long-term follow-up in this patient subset.…”
Section: Discussionsupporting
confidence: 87%
“…Data on the elderly from the Danish nationwide cohort study clearly show how age ≥75 years represents a particularly high-risk patient group for recurrent stroke/thromboembolism. 21 Of note, previous CAD, aspirin use, and poor TTR control also emerged as independent predictors for any clinically relevant bleeding among anticoagulated patients with AF.…”
Section: November 2015mentioning
confidence: 98%